Theoretical formulations and computational modeling of flexible circuit's behaviour - Loh, Tick Boon. (2009)
In this report, an in-depth study on the behaviour of the Hewlett-Packard flexible circuit when cooled from the elevated curing temperature to room temperature is presented. The purpose of this study is to develop a mathematical model using the Classical Laminate Theory in conjunction with the minimum Total Potential Energy approach for the purpose of predicting the shapes and curvatures of the Hewlett-Packard flexible circuit caused by the effect of thermal stress induced during the lamination process. The mathematical model is programmed using Maple software and the results are presented graphically in 3D plots. Results are then compared with those from several other investigators, and limited Finite Element Analysis is used to further study the problem.